(untitled) (MAUSAM, 2003)
The study examines the performance of INSAT derived quantitative precipitation estimates( QPE) for different varying synoptic conditions and also presents a quantitative assessment of spatial and seasonal characteristics of these errors over Indian region making detailed inter-comparison with land rainfall observations. The study reveals that the QPE, in general, is able to capture rainfall pattern associated with different synoptic conditions and spatial distribution of mean rainfall of each season. But it has certain seasonal and spatial biases. The rainfall over most part of the country south of Lat. 30° N is under-estimated in all seasons except pre-monsoon. For the region north of Lat. 30 ° N where western disturbances are dominant, rainfall is over estimated. In the convective season of pre-monsoon, QPE has got very high degree of correspondence with the observed rainfall.